Fenfluramine HCl (Fintepla®) provides long‐term clinically meaningful reduction in seizure frequency: Analysis of an ongoing open‐label extension study. (19th October 2020) - Sullivan, Joseph; Scheffer, Ingrid E.; Lagae, Lieven; Nabbout, Rima; Pringsheim, Milka; Talwar, Dinesh; Polster, Tilman; Galer, Bradley; Lock, Michael; Agarwal, Anupam; Gammaitoni, Arnold; Morrison, Glenn; et al.
Abstract: Objective: Fenfluramine has been shown to provide clinically meaningful and statistically significant reductions in convulsive seizure frequency in children and adolescents (aged 2‐18 years) with Dravet syndrome in two randomized, placebo‐controlled clinical trials. The objective of this analysis was to assess longer‐term safety and efficacy of fenfluramine in patients who completed one of the double‐blind studies and entered an open‐label extension (OLE) study. Methods: Patients enrolling in the OLE study initiated fenfluramine at 0.2 mg/kg/d regardless of their treatment assignment in the double‐blind study. After 4 weeks, the fenfluramine dose could be titrated based on efficacy and tolerability to maximum of 0.7 mg/kg/d (absolute maximum 27 mg/d) or maximum of 0.4 mg/kg/d (absolute maximum 17 mg/d) in patients receiving concomitant stiripentol. The number and type of seizures were recorded daily in an electronic diary, and safety, including echocardiography, was assessed at Months 1, 2, and 3, and at 3‐month intervals thereafter. Results: A total of 232 patients were enrolled as of March 13, 2018. During this analysis period, patients were treated for a median 256 days (range = 46‐634 days). Over the entire OLE analysis period, the median decrease in convulsive seizure frequency compared to baseline in the double‐blind studies was −66.8% (range = −100% to 234.9%; P < .001). The median reduction in seizure frequency was similar in patients <6 (−75.7%) and ≥6 years old (−64.7%). The most commonly reported adverse events included pyrexia (21.6%), nasopharyngitis (19.4%), and decreased appetite (−15.9%). No valvular heart disease (VHD) or pulmonary arterial hypertension (PAH) was observed. Significance: Study results demonstrate that fenfluramine provides clinically meaningful (≥50%) seizure frequency reduction over an extended period in patients with Dravet syndrome. No patient developed VHD or PAH, and fenfluramine was generally well tolerated.